1999
DOI: 10.1002/(sici)1097-4636(199910)47:1<91::aid-jbm13>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive glasses induce chemiluminescence by human polymorphonuclear leukocytes

Abstract: The effect of bioactive glasses on human polymorphonuclear leukocytes (PMNLs) were studied in vitro by a chemiluminescence (CL) assay. Eight different glasses were chosen. All glasses induced a rapid CL response by human PMNLs, which proved to be dose dependent. The CL response also seemed to depend on the durability of the glasses. The least durable glass caused the highest CL response, and highly durable glasses caused only low CL responses by the cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In a previous study we demonstrated that bioactive glasses can induce release of ROMs by PMNLs. 8 In this study it is demonstrated that the response of PMNLs to HA crystals is low compared to that of the bioactive glass.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…In a previous study we demonstrated that bioactive glasses can induce release of ROMs by PMNLs. 8 In this study it is demonstrated that the response of PMNLs to HA crystals is low compared to that of the bioactive glass.…”
Section: Discussionmentioning
confidence: 77%
“…The final fraction of glass consisted mostly of particles < 5 m and was obtained by using the gravimetric sedimentation method. 8 A mixture of glass powder and ethanol was shaken in a test tube, and after sedimentation for 1 min, the heaviest particles were separated by pipetting 90% of the dispersion. The dispersion was moved to another test tube filled with ethanol.…”
Section: Glass Preparationmentioning
confidence: 99%
See 1 more Smart Citation